The Perks of Being a Teenager: Exploring the Role of Self-Control in Juvenile Delinquency – A Literature Review - Windani Tiarahmawati; Iriani Indri Hapsari; Mira Ariyani; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
Adolescence is a critical developmental stage marked by emotional volatility and identity exploration. However, not all adolescents navigate this phase successfully many exhibit risky behaviors categorized as juvenile delinquency. This literature review aims to examine the role of self-control in adolescent delinquency by exploring the types of delinquent behaviors associated with low self-control, identifying environmental factors that influence self-control, and analyzing the educational and psychosocial implications of these findings. Using articles published between 2020 and 2025 sourced from Google Scholar, Scopus, and EBSCO, a total of 11 relevant studies were reviewed. The analysis revealed that low self-control significantly contributes to aggressive behavior, substance abuse, cyberbullying, and sexual offenses among youth. Furthermore, external factors such as permissive parenting, deviant peer influence, and punitive school discipline were found to weaken self-control, whereas consistent parental attachment and supportive school environments can strengthen it. This review highlights the need for integrated interventions involving family, schools, and community support systems to enhance adolescents' self-control capacities and reduce delinquent behaviors. These findings support the theoretical framework of self-control theory while emphasizing the interplay between individual psychological traits and environmental contexts.